Pengaruh Konten Instagram @Makanansmr Terhadap Meningkatkan Brand Awareness Hidden Wings - Firnanda, Febri; Boer, Kheyene Molekandella; Rohmah, Ainun Ni'Matu; Purwanti, Silviana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The purpose of this study was to analyze the effect of @Makanansmr Instagram content on increasing Hidden Wings brand awareness. This type of research is quantitative. The data collection techniques used in this research are library research and questionnaires. The population of this study are @makanansmr followers who watch hidden wings review content impressions. Determination of the sample in this study using the Lemeshow formula. The number of samples in this study were 100 respondents. The data analysis technique used is quantitative with the help of SPSS 24 software. The result of this study is that there is a significant relationship between the content posted on the @makanansmr Instagram account and Brand Awareness for the